Targeted Muscle Reinnervation in Children: A Case Report and Brief Overview of the Literature. Issue 12 (17th December 2021) - Pires, Giovanna R.; Moss, Whitney D.; Ormiston, Laurel D.; Baschuk, Christopher M.; Mendenhall, Shaun D.
Abstract : Summary: Absence of the proximal upper limb, whether congenital or acquired, has a profound impact on quality of life. Targeted muscle reinnervation (TMR) was originally developed to improve functional control over myoelectric prostheses; however, it has also been shown to decrease phantom limb pain and neuroma pain as well as prevent neuroma formation. In children, whose rates of prosthetic use are considerably lower than adults, the effects of amputation on limb function can be devastating. To date, there is very little literature regarding the use of TMR in children. In this case report, we review the current literature and present the case of a 9-year-old boy with a transhumeral amputation secondary to a traumatic injury who underwent acute TMR at the time of wound closure. At 22 months follow-up, the patient is doing well with minimal pain, no evidence of neuroma formation, and signs of muscle reinnervation.